2010
DOI: 10.21083/partnership.v5i1.1012
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Populations in Saskatchewan: The Challenges of Reaching Them

Abstract: Saskatchewan is more diverse than it was even 5 years ago. Although historically Saskatchewan has always had a diverse immigrant population, with immigrants from many European and Eastern European countries, recently there have been other large immigrant communities arriving from several parts of the globe through various significant government initiatives and policies; some as refugees, some as guest workers, some as international students with their families. Not only is this diverse immigrant population gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The TPL can potentially serve as a model library for other institutions through their ML collection development strategies. In their article, Kumaran and Salt (2010) concluded that compared to other large, urban library systems, TPL was the most dedicated to their diverse community based on their non-English services and community partnerships. Nevertheless, the results of this study reveal that at the time of data collection the TPL ML collection was far from proportional in representation to the population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The TPL can potentially serve as a model library for other institutions through their ML collection development strategies. In their article, Kumaran and Salt (2010) concluded that compared to other large, urban library systems, TPL was the most dedicated to their diverse community based on their non-English services and community partnerships. Nevertheless, the results of this study reveal that at the time of data collection the TPL ML collection was far from proportional in representation to the population.…”
Section: Discussionmentioning
confidence: 99%
“…The Reference and User Services Association's (1990) "Guidelines for Multilingual Materials Collection and Development and Library Services" echo that statement, relating the size of the collection to the size of the group; however, the updated 2007 "Guidelines for the Development and Promotion of Multilingual Collections and Services" version removes that wording from their guidelines. While it is important to compare the language collection to the population that speaks that language, there is a move away from what a "balanced" collection may refer to; rather, the goal of collection development is about meeting the needs of the user groups within the given constraints (Dali, 2010;Kumaran & Salt, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Canadian Employment Equity Act (Government of Canada, 2014) uses the term "Visible Minorities" and defines them as "persons, other than Aboriginal peoples, who are non-Caucasian in race or non-white in colour" (Statistics Canada, 2012a (Fox, 2007;Ingles et al, 2005;McKenna, 2007), papers on the importance of diversity among Canadian librarians (Kandiuk, 2014;Leong, 2013), papers on multicultural populations, services, and collections (Berry, 2008;Chilana, 2001;Cho & Con, 2012;Dilevko & Dali, 2002;Kumaran & Salt, 2010;Paola Picco, 2008), and articles on information seeking behaviour or information practices of immigrants (Caidi, 2008;Caidi & MacDonald, 2008;Hakim Silvio, 2006) and reading practices of Canadian immigrants (Dali, 2012).…”
Section: Research Backgroundmentioning
confidence: 99%